2014
DOI: 10.3390/molecules19056583
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Enhances the Antibacterial Activity of Selected Antibiotics against Coagulase-Negative Staphylococcus Strains in Vitro

Abstract: Synergistic interactions between commonly used antibiotics and natural bioactive compounds may exhibit therapeutic benefits in a clinical setting. Berberine, an isoquinoline-type alkaloid isolated from many kinds of medicinal plants, has proven efficacy against a broad spectrum of microorganisms. The aim of the presented work was to assess the antibacterial activity of berberine chloride in light of the effect exerted by common antibiotics on fourteen reference strains of Staphylococccus spp., and to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 27 publications
3
66
0
Order By: Relevance
“…A Recent study indicates that the primary mechanism of antibacterial action of berberine is due to inhibition of the cell division protein FtsZ (Boberek et al ., ). Berberine has a synergistic effect with some common antibiotics especially with linezolid, cefoxitin, and erythromycin (Wojtyczka et al ., ). This suggests the potential use of berberine in combinations with other antibiotics as an efficient therapeutic tool for antibiotic‐resistant bacterial infections.…”
Section: Antimicrobial Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…A Recent study indicates that the primary mechanism of antibacterial action of berberine is due to inhibition of the cell division protein FtsZ (Boberek et al ., ). Berberine has a synergistic effect with some common antibiotics especially with linezolid, cefoxitin, and erythromycin (Wojtyczka et al ., ). This suggests the potential use of berberine in combinations with other antibiotics as an efficient therapeutic tool for antibiotic‐resistant bacterial infections.…”
Section: Antimicrobial Effectsmentioning
confidence: 97%
“…Berberine is widely used as an anti‐infective in traditional medicine (Boberek et al ., ). Berberine has been shown to exhibit antibacterial activity against a variety of bacteria, including Streptococcus agalactiae (MIC = 78 mug/mL) (Peng et al ., ), Actinobacillus pleuropneumoniae (MIC = 0.3125 mg/mL) (Kang et al ., ), different strains of Staphylococccus (MIC = from 16 to 512 micro g/mL) (Wojtyczka et al ., ) and, Shigella dysenteriae (Kong et al , ). Berberine also effectively prevents the formation of S .…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…Berberine, an isoquinoline alkaloid, has been used for traditional medical systems in eastern countries. It possesses several biological activities including anti-inflammatory (Chu et al, 2014), anticancer (Yip and Ho, 2013;Cai et al, 2014), anti-diabetic (Rajendran et al, 2014), antibacterial (Wojtyczka et al, 2014), and antifungal functions (Zhu et al, 2014). The antioxidant capacity of berberine has demonstrated both direct (Jang et al, 2009;Bashir and Gilani, 2011) and indirect activities (Hwang et al, 2002;Tan et al, 2007).…”
Section: Antioxidant Effect Of Berberine and Its Phenolic Derivativesmentioning
confidence: 99%
“…Kang et al [48] reported that berberine exhibited time and concentration dependence antibacterial activity against Actinobacillus pleuropneumoniae with the MIC of 0.3125 mg/mL. Wojtyczka et al [50] reported that berberine has antibacterial activity against coagulase-negative staphylococcus strains with the MIC ranged from 16 to 512 μg/mL. The higher bactericidal effect of CA/Gel/Beri dressing observed in our study is related to the incorporation berberine in the matrix of CA/Gel nanofibers, while this value is effective for wound dressing applications.…”
Section: Antibacterial Assay Findingsmentioning
confidence: 99%